2019
DOI: 10.3389/fonc.2019.00121
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Intravesical Bacille Calmette-Guérin and Chemotherapy vs. Bacille Calmette-Guérin Alone in Non-muscle Invasive Bladder Cancer: A Meta-Analysis

Abstract: Background: About 75% of newly diagnosed bladder cancer cases suffer from non-muscle invasive bladder cancer (NMIBC), which used to recur and progress despite transurethral resection of bladder tumor (TURBT). This meta-analysis was conducted to examine if combined application of intravesical bacille Calmette-Guérin (BCG) with chemotherapy is associated with better prognosis. Methods: Systematic searches of randomized controlled trials (RCTs) concerning NMIBC were performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Moreover, side effects were significantly decreased in patients who received BCG plus chemotherapy. 77 The efficacy of intravesical therapies can also be improved through delivery adaptations such as hyperthermia, electromotive drug administration or new devices.…”
Section: Chemotherapeutic Treatments and Improved Deliverymentioning
confidence: 99%
“…Moreover, side effects were significantly decreased in patients who received BCG plus chemotherapy. 77 The efficacy of intravesical therapies can also be improved through delivery adaptations such as hyperthermia, electromotive drug administration or new devices.…”
Section: Chemotherapeutic Treatments and Improved Deliverymentioning
confidence: 99%
“…In a murine model, acetylic salicylic acid and pentoxifylline seem to be effective in improving BCG efficacy [92]. In a systemic meta-analysis, it was concluded that compared to BCG alone, the synergistic effect of intravesical BCG and chemotherapy improved recurrence free survival, overall survival and disease specific survival with significantly decreased rate of fever, irritative symptoms and hematuria therapy among NMIBC patients [93]. Nonetheless, the therapeutic efficacy of BCG is undermined owing to its associated local and systemic side effects such as dysuria, haematuria, cystitis, sepsis, malaise and fever [83,90].…”
Section: Intravesical Immunotherapy With Bcgmentioning
confidence: 99%
“…A debated point which requires intense further investigation is to understand if BCG substrains, generated over time, could alter the host response. The main substrains used are Russia, Moreau, Japan, Sweden, and Birkhaug (elimination of region of differentiation 1) and BCG Prague, Glaxo, Danish, Tice, Frappier, and others (deletion region of differentiation 2) (Hayashi et al, 2010;Kasempimolporn et al, 2018). However, findings available so far are not sufficient to support more effectiveness of specific BCG strain over another.…”
Section: Bacillus Calmette-guérin Intravesical Therapymentioning
confidence: 99%
“…- Intravesical chemotherapeutic drugs , alone or in combination, are used for high-risk NMIBC such as pirarubicin, gemcitabine, and epirubicin (Kang et al, 2016 ); intravesical application of mitomycin C is a chemotherapeutic agent most used in patients who do not respond to BCG (Fankhauser et al, 2020 ). The latter approach is also useful for patients who have developed significant side effects; the combination of BCG treatment with chemotherapeutic agents has demonstrated the reduction of side effects and an improvement of tolerability to BCG (Huang et al, 2019 ).…”
Section: Modern Anticancer Therapymentioning
confidence: 99%